COHESION ANALYSIS OF ISLAMIC READING TEXTBOOKS - Fadlilah, Sayyidatul (English Department of Faculty of Tarbiyah and Teacher Training, 2014)
There are many students of Islamic Education and Teacher Training Facultyof IAIN Walisongo Semarang who have complained that Islamic reading texts used by their teachers are hard for them to understand. I examine this issue by seeing some linguistic aspects of those reading texts. This Qualitative and Descriptive approach highlighted the types of grammatical and lexical cohesive devices and the realization of cohesiveness of those reading textsbased on Halliday and Hasan?s theory.The result of the study shows that the six reading texts (A.1, 2, 3; and B.1, 2, 3) stated in reading textbooks: English for Islamic Studies, English for Islamic Studies 2, Understanding Islam; for Islamic Studies; in terms of cohesion (following Halliday and Hasan?s principles of reading texts) respectively the average score of anaphoric references: 54.17% for text A.3, 53.85% for text B.2, 53.06% for text A.1, 48.57% for text B.3, 41.86% for text B.1, 33.33% for text A.3. After consulting to the Halliday and Hasan?s principles of cohesion of the reading texts (1989), that the most cohesive reading texts is text A.3, whereas the least cohesive one is Text A.2. Finally, these factors will assist lecturers and students in choosing the appropriate book for them.